Effect of 4.77% and 4.7% Alcoholic Drinks on Surface Roughness of Resin-Modified Glass Ionomer Cement - Margaretta, Dewi Liliany; Adis, Zaldy Farhan (Indonesian Dental Association, 2021)
Introduction: Resin-modified glass ionomer cement (RMGIC) is a hybrid restorative material that combines resin and glass ionomer cement (GIC). The addition of hydroxyethyl methacrylate (HEMA) to RMGIC improves its physical properties, such as resistance to surface roughening. Food and drink often produce factors that trigger surface roughening. Beverages with alcohol contents of 4.77% and 4.7%, which are widely consumed by Indonesians, have acidic pH values. Rough surfaces promote bacterial adhesion and plaque accumulation, inducing secondary caries. Objective: The aim of the present study was to determine the difference in the surface roughness of RMGIC after immersion in beverages with alcohol contents of 4.77% and 4.7%. Methods: Twenty-two samples (diameter = 10 mm; height = 2 mm) were divided into three groups: Group I comprised eight samples of RMGIC soaked in a beverage with an alcohol content of 4.77%; Group II comprised eight samples of RMGIC soaked in a beverage with an alcohol content of 4.7%; and Group III comprised six samples of RMGIC soaked in distilled water as a control. Groups I and II were immersed for 34 min twice per day. The RMGIC was immersed in an incubator at 37°C for 21 days. The samples were then tested using Surface Roughness Tester S-100. Results: Each group had a different mean roughness value. One-way analysis of variance (ANOVA) and Tukey’s post hoc analysis test indicated a significance value of p = 0.021. Tukey’s post hoc analysis test revealed a significant difference in surface roughness between the RMGIC samples soaked in the beverage with an alcohol content of 4.77% and those soaked in distilled water. Conclusion: The beverage with an alcohol content of 4.77% produced a higher surface roughness value than the beverage with an alcohol content of 4.7% or the control over 21 days.